Lethal and sublethal effects of ammonia in deuterodon iguape (Eigenmann 1907), potential species for Brazilian aquaculture - Barbieri, Edison; Lenz, Rafaela Marina; de Nascimento, América Andrade; de Almeida, Genésio Lopes; Roselli, Larissa Yoshida [UNESP]; Henriques, Marcelo Barbosa (Boletim do Instituto de Pesca, 2019)
The cultivation of the lambari, Deuterodon iguape, supplies much of the Brazilian market with live bait for sport fishing. The high densities used to maximize production can increase the concentration of ammonia. In order to evaluate the sublethal and lethal effects of different concentrations of ammoniacal nitrogen (non-ionized ammonia plus ionized ammonia), D. iguape were exposed to this xenobiotic. The LC 50 values for 24, 48, 72, 96 h of ammonia-N were 6.17, 5.57, 3.88 and 2.90 mg/L at 23°C. The LC 50 values of 24, 48, 72, 96 h of NH 3 -N (non-ionized ammonia with nitrogen) were 0.015; 0.013; 0.009; 0.007 mg/L. The specific oxygen consumption increased at the ammonia-N concentrations tested. The values for the concentrations of 0.1; 0.25; 0.5 and 1.0 mg/L were: 0.25, 0.33; 0.31 and 0.44 mgO 2 /g/hr. At the concentration of 1.0 mg/L of ammonium chloride there was a 41.33% increase in the consumption level in relation to the control. Ammonia excretion also increased with increasing ammoniacal nitrogen concentration. The fish excreted, on average, 0.0320, 0.0364, 0.0368 and 0.0370 mg/g/h of ammonia. Comparing these results with the means of ammonia excretion of the control (0.0 mg/L), it was observed that these values represent an increase in the excretion of 146%, 177%, 189% and 184%, respectively. After 24 h of exposure to ammonia, the O:N ratio decreased by 43.46%. Our results indicate pronounced metabolic effects and increased toxicity with increasing ammonia concentrations. We recommend avoiding concentrations higher than 0.25 mg/L NH 3 -N in the culture water.
Efeito letal e subletal da amônia sobre o lambari (Deuterodon iguape, eigenmann 1907), espécie potencial para a aquicultura Brasileira
Keywords: Aquaculture; Lambari; LC 50; Nitrogenous compounds; O:N ratio